Implementation of Local Content of Banten Javanese Language in the Independent Curriculum in Elementary Schools - Fajriati, Nurul; Holisoh, Iis; Muttaqin, Ahmad; Dewi, Ratna Sari (CV. Pusdikra Mitra Jaya, 2024)
This study aims to analyze the implementation of local content of Banten Javanese Language in the Independent Curriculum at SDN Kewunen, Serang, Banten. The selection of Banten Javanese as a local content at SDN Kewunen is based on efforts to preserve the Banten Javanese language. The research method used is a case study with a qualitative approach Data collection techniques are carried out through in-depth interviews, observations, and documentation. The results of the implementation research are still faced with various obstacles, the limitation of teaching materials, the lack of interactive learning media and the majority of teachers feel that further training is needed to improve the quality of teaching. Students tend to show a positive attitude towards this learning, but limited learning methods lead to less than optimal their understanding and engagement. The development of adequate teaching materials, a variety of learning methods, and more diverse evaluations are needed to increase the effectiveness of Banten Javanese language learning in elementary schools.